Continuous Flow Synthesis of Azoxybenzenes by Reductive Dimerization of Nitrosobenzenes with Gel‐Bound Catalysts. Issue 11 (4th March 2021) - Schmiegel, Carsten J.; Berg, Patrik; Obst, Franziska; Schoch, Roland; Appelhans, Dietmar; Kuckling, Dirk
Abstract: In the search for a new synthetic pathway for azoxybenzenes with different substitution patterns, an approach using a microfluidic reactor with gel‐bound proline organocatalysts under continuous flow is presented. Herein the formation of differently substituted azoxybezenes by reductive dimerization of nitrosobenzenes within minutes at mild conditions in good to almost quantitative yields is described. The conversion within the microfluidic reactor is analyzed and used for optimizing and validating different parameters. The effects of the different functionalities on conversion, yield, and reaction times are analyzed in detail by NMR. The applicability of this reductive dimerization is demonstrated for a wide range of differently substituted nitrosobenzenes. The effects of these different functionalities on the structure of the obtained azoxyarenes are analyzed in detail by NMR and single‐crystal X‐ray diffraction. Based on these results, the turnover number and the turnover frequency were determined. Abstract : In search for a new synthetic pathway for azoxybenzenes with different substitution patterns, an approach using a microfluidic reactor with gel‐bound proline organocatalysts under continuous flow inside a microfluidic device is presented.